Post a New Question

Trig

posted by .

Prove sin(α+β)sin(α-β)=cos^2β-cos^2α

  • Trig -

    First off these are usually not this hard...just saying...ill be changing your alphas to x's and your betas to y's

    we will work with the left side because it is easier.

    use identity sum and difference
    sin(x+y)sin(x+y)=cos^2y-cos^2x
    s

  • Trig -

    (sinxcosy+cosxsiny)(sinxcosy-cosxsiny)=
    Then, foil those and your middle two terms should cancel out leaving you with
    sin^2xcos^2y-cos^2xsin^2y=
    now using the pythagereom theorem change all the sin^2's to cos^2 giving you
    cos^2y-cos^2xcos^2y-[cos^2xcos^2xcos^2y]=

    cos^2y-cos^2xcos^2y-cos^2x+cos^2xcos^2y=

    cos^2y-cos^2x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question